Immunogenicity and protective efficacy of a live attenuated H5N1 vaccine in nonhuman primates. - Fan, S; Gao, Y; Shinya, K; Li, C; Li, Y; Shi, J; Jiang, Y; Suo, Y; Tong, T; Zhong, G; Song, J; Zhang, Y; et al. (Public Library of Science, 2009)
The continued spread of highly pathogenic H5N1 influenza viruses among poultry and wild birds, together with the emergence of drug-resistant variants and the possibility of human-to-human transmission, has spurred attempts to develop an effective vaccine. Inactivated subvirion or whole-virion H5N1 vaccines have shown promising immunogenicity in clinical trials, but their ability to elicit protective immunity in unprimed human populations remains unknown. A cold-adapted, live attenuated vaccine with the hemagglutinin (HA) and neuraminidase (NA) genes of an H5N1 virus A/VN/1203/2004 (clade 1) was protective against the pulmonary replication of homologous and heterologous wild-type H5N1 viruses in mice and ferrets. In this study, we used reverse genetics to produce a cold-adapted, live attenuated H5N1 vaccine (AH/AAca) that contains HA and NA genes from a recent H5N1 isolate, A/Anhui/2/05 virus (AH/05) (clade 2.3), and the backbone of the cold-adapted influenza H2N2 A/AnnArbor/6/60 virus (AAca). AH/AAca was attenuated in chickens, mice, and monkeys, and it induced robust neutralizing antibody responses as well as HA-specific CD4+ T cell immune responses in rhesus macaques immunized twice intranasally. Importantly, the vaccinated macaques were fully protected from challenge with either the homologous AH/05 virus or a heterologous H5N1 virus, A/bar-headed goose/Qinghai/3/05 (BHG/05; clade 2.2). These results demonstrate for the first time that a cold-adapted H5N1 vaccine can elicit protective immunity against highly pathogenic H5N1 virus infection in a nonhuman primate model and provide a compelling argument for further testing of double immunization with live attenuated H5N1 vaccines in human trials.